2020
DOI: 10.1159/000507228
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Asthma and Bronchiectasis: State of the Art

Abstract: The nonrecognition of asthma-associated comorbidities is often responsible for the therapeutic failure and the worsening of symptoms, and it is associated with frequent exacerbations, higher disease severity, and increased health costs. Bronchiectasis, one of the most frequent asthma-associated comorbidities, can increase airways inflammation and exacerbation rates and cause respiratory functional impairment. The aim of this article is to review the interactions between bronchiectasis and asthma, in order to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 142 publications
(204 reference statements)
0
32
0
2
Order By: Relevance
“…Many studies have been published on CBI by P. aeruginosa in bronchiectasis and people with COPD but only a few have evaluated the isolation of bacterial pathogens in the respiratory secretions of people with asthma. People with severe asthma can present both bronchiectasis and CBI by various pathogens, but they are often not subjected to a microbiological study, thereby complicating the management of their disease and hindering a successful therapy [210,211]. In such people, the presence of uncontrolled bronchial inflammation can lead to increased production of respiratory secretions, with a consequent formation of mucous blockages, leading to local damage to the bronchial mucus and P. aeruginosa the development of bronchiectasis.…”
Section: Pseudomonas Aeruginosa and Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been published on CBI by P. aeruginosa in bronchiectasis and people with COPD but only a few have evaluated the isolation of bacterial pathogens in the respiratory secretions of people with asthma. People with severe asthma can present both bronchiectasis and CBI by various pathogens, but they are often not subjected to a microbiological study, thereby complicating the management of their disease and hindering a successful therapy [210,211]. In such people, the presence of uncontrolled bronchial inflammation can lead to increased production of respiratory secretions, with a consequent formation of mucous blockages, leading to local damage to the bronchial mucus and P. aeruginosa the development of bronchiectasis.…”
Section: Pseudomonas Aeruginosa and Asthmamentioning
confidence: 99%
“…In such people, the presence of uncontrolled bronchial inflammation can lead to increased production of respiratory secretions, with a consequent formation of mucous blockages, leading to local damage to the bronchial mucus and P. aeruginosa the development of bronchiectasis. People with coexisting bronchiectasis and asthma tend to be older, with a longer duration of asthma, greater airway inflammation and functional decline, more frequent exacerbations and, therefore, greater disease severity [211][212][213][214][215][216][217][218][219]. Studies that have analyzed the cultures of respiratory secretions of people with asthma have found that the presence of bacteria in the sputum is associated with a longer duration of the disease, poorer lung function (FEV1), and more neutrophils and a higher concentration of Il-8 in the sputum [219,220].…”
Section: Pseudomonas Aeruginosa and Asthmamentioning
confidence: 99%
“…In patients who never had TB, it was observed that they had chronic lung diseases like bronchial asthma and chronic obstructive pulmonary disease (COPD) which predisposed them to develop bronchiectasis [12]. There was one patient with congenital intra-lobar sequestration, colonised by the fungus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our data revealed that COPD, bronchiectasis, and anxiety were associated with EPA. It emphasized the necessity to raise awareness and make correct diagnosis of these comorbidities among clinicians to guide an appropriate treatment strategy in these patients with EPA [57, 58]. This suggests that comorbidity varies among races.…”
Section: Discussionmentioning
confidence: 99%